2006
DOI: 10.1111/j.1439-0442.2006.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Binding Capacity of Zeolite A to Calcium, Phosphorus and Magnesium in Rumen Fluid as Influenced by Changes in pH

Abstract: An in vitro experiment was designed to mimic the transport of ingested zeolite A in the forestomachs and proximal part of the small intestine so as to evaluate the binding capacity of zeolite A to Ca, P and Mg as influenced by changes in pH. This was done by incubation of rumen fluid solutions with and without zeolite, as well as varying the content of Ca and/or P. The pH was lowered by addition of HCl so as to mimic abomasal conditions, followed by subsequent HCO3- addition to mimic small intestinal pH. Rumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…On the other hand, in an in vitro study, researchers revealed significant effects of zeolite A addition to ruminal fluid at different levels of pH similar to various sections of alimentary tract. The authors believed that these changes could be resulted to hypomagnesaemia in vivo [21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, in an in vitro study, researchers revealed significant effects of zeolite A addition to ruminal fluid at different levels of pH similar to various sections of alimentary tract. The authors believed that these changes could be resulted to hypomagnesaemia in vivo [21].…”
Section: Discussionmentioning
confidence: 98%
“…A low level of supernatant phosphorus was maintained after HCO −3 addition. Neutralization by HCO −3 led to a zeolite-induced drop in supernatant Ca and Mg [21]. In general, clinoptilolite is considered to be rather stable in the acid environment of the stomach without undergoing major degradation during its transit through the digestive tract [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cows with a zeolite A supplementation in doses higher than 300 g/d showed a hypophosphataemia (Thilsing-Hansen et al 2002Enemark et al 2003;Grabherr et al 2008Grabherr et al , 2009Pallesen et al 2008). An addition of zeolite A to rumen fluid in vitro led to a decrease of supernatant phosphorus concentration after acidification with hydrochloric acid (Thilsing et al 2006). At acid pH, zeolite A may be destroyed releasing silicic acid, amorphous aluminium silicate and aluminium (Cook et al 1982).…”
Section: Introductionmentioning
confidence: 98%
“…In accordance with these findings, Enemark et al (2003) presented significantly lower Mg concentrations in serum of treated dry cows compared with control group. Furthermore Thilsing et al (2006) showed in an in vitro study, a zeolite-induced reduction of Mg in supernatants of rumen fluid. On the contrary, Pallesen et al (2008) observed no differences of serum Mg concentrations during zeolite application.…”
Section: Discussionmentioning
confidence: 94%
“…In an in-vitro study, Thilsing et al (2006) showed that zeolite might bind Ca in the rumen, but could release it again in the abomasum. Perhaps the capacity of zeolite to bind Ca in the rumen, especially in combination with the above mentioned release, might be too small to have a relevant effect on the Ca homeostasis of the goats.…”
Section: Discussionmentioning
confidence: 99%